Optimization of mean inter-element distance in aperiodic sparse linear phased array antennas - Aldaya, Ivan [UNESP]; Dias, Bruna [UNESP]; Santos, Mirian P. [UNESP]; De Oliveira, José A. [UNESP]; Abbade, Marcelo L. F. [UNESP]; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Sparse linear arrays are attractive when high directivity and low cost should be simultaneously achieved, when near field coupling must be avoided, or when physical constraints limit the minimum separation between elements. However, uniformly distributed sparse arrays present strong side lobes that may cause severe interference and security faults. Thus, the non-uniform arrangement of elements has been extensively proposed to reduce the side lobe level (SLL). In this paper, we present numerical results revealing that when a minimum inter-element separation is considered, there is an optimum mean distance that minimizes the SLL of the array.